Cracking the Deck: National origins and promotions in the Dutch East India Company, 1700–1796 - Wezel, Filippo Carlo; Ruef, Martin (Organization studies, 2024)
Organizational scholars highlight various challenges in reducing inequality within organizations. Due to unanticipated consequences, many programs launched by organizations fail to accomplish this goal. We leverage historical data from the Dutch East India Company to claim that training programs may be an effective tool against inequality when coupled with teamwork incentives and included in broader programs for change. We study the effects of these programs on the unequal promotion rates between Dutchmen and non-Dutchmen across periods of time in which those programs were offered and in which they were not. Our analyses of promotions to top-ranked positions on the Company’s ships suggest a two-fold conclusion: first, the introduction of leadership training and teamwork incentives reduced the differential weights given to the experience of Dutchmen and non-Dutchmen; and, second, those benefits disappeared when the policies were rescinded. The results underscore the opportunities and difficulties that organizations face in implementing durable interventions against inequality.